Low-Frequency Pulse Width Modulation Control Methods of Ultrasonic Motor - Shi Jingzhuo; Zhang Caixia (Institute of Advanced Engineering and Science, 2013)
Because of the serious non-linearity and coupling among state variables caused by the complex energy conversion process in ultrasonic motor, the motion control strategy of ultrasonic motor still need to be studied in detail to obtain better performance. As a kind of special control method, the low-frequency PWM control strategy can make the on-line optimum control easier, and may be an effective means to realize high performance motion control using ultrasonic motor. But this kind of strategy has not been studied in detail until now. This paper analyzes the difference among three low-frequency PWM control methods in details, works out the principle of selection among these methods. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3262